EFFECT OF PHAGOTHERAPY IN A PATIENT WITH ATOPIC DERMATITIS: A CLINICAL CASE STUDY - Гладков, Сергей Федорович; Перевощикова, Нина Константиновна; Черных, Наталья Степановна (Mother and Baby in Kuzbass, 2024)
As one of the most common dermatoses in children, atopic dermatitis (AD) is a multifactorial immune-mediated disorder caused by complex mechanisms of interaction between genetic and environmental factors. The dominant role in the formation of atopy, of course, belongs to the genetic component, but the leading trigger predictors invariably remain external environmental factors. The defining environmental component of atopy is infection, the delicate management of which makes it possible to control atopic march (AM). Current research emphasizes the potential of bacteriophages in modeling the gut microbiota of children in the first months of life, allowing very effective management of AM.
Keywords: atopic dermatitis; atopic march; gut microbiota; bacteriophages; decontamination; treatment; prevention